2014
DOI: 10.1002/hfm.20557
|View full text |Cite
|
Sign up to set email alerts
|

Signage Versus Environmental Affordances: Is the Explicit Information Strong Enough to Guide Human Behavior During a Wayfinding Task?

Abstract: This study aims to explore how people behave when they have to find a location within a complex building and are confronted with situations where directional signage (i.e., explicit information) is in opposition to environmental affordances that naturally direct users towards a specific path, creating a situation with conflicting information (e.g., a brighter corridor vs. a darker corridor but with a directional sign indicating to follow the darker one). A virtual reality–based methodology was used and a betwe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 21 publications
0
20
0
Order By: Relevance
“…Different attributes of corridors and choice pattern of people at intersections were examined in two studies and findings showed that in the absents of signs, people are more likely to choose wider and brighter corridors at T-type intersection (nodes with two alternatives of turning left or right), but not necessarily at F-type intersections (nodes with two alternatives of continuing straight or turning right/left) during non-emergency situations. However, people relied on signs when they were available ( Vilar et al, 2014b , 2015 ).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Different attributes of corridors and choice pattern of people at intersections were examined in two studies and findings showed that in the absents of signs, people are more likely to choose wider and brighter corridors at T-type intersection (nodes with two alternatives of turning left or right), but not necessarily at F-type intersections (nodes with two alternatives of continuing straight or turning right/left) during non-emergency situations. However, people relied on signs when they were available ( Vilar et al, 2014b , 2015 ).…”
Section: Resultsmentioning
confidence: 99%
“…In a series of experiments, Van Tilburg and Igou (2014) examined which of four heuristics—the action-continuation heuristic, the initial segment heuristic, the least-angle heuristic, and the hill-climbing heuristic—individuals preferred while navigating a maze with equally functional routes at a choice point and found that participants behaved in a way consistent with use of the action-continuation heuristic. In three other studies, navigation patterns of people were investigated in two types of intersections: T-type intersections (nodes with two alternatives of turning left or right) and F-type intersections (nodes with two alternatives of continuing straight or turning right/left) ( Vilar et al, 2012 , 2014b , 2015 ). Findings showed that the type of intersection affected people’s behavior, such that brighter corridors were preferred at both T-type and F-type intersections and wider corridors at only T-type intersections.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations